Vai trò của sách, báo cách mạng trogn quá trình tìm đường cứu nước của Nguyễn Ái Quốc (1911-1930) - Quý, Trần Thị (VNU Journal of Science: Social Sciences and Humanities; Vol 20 No 1, 2004)
During the two decades of looking for the Vietnamese way to national salvation (1911- 1930) in Nguyen Ai Quoc’s revolutionary life, revolutionary books and journals did play an extremely significant role. Books and journals were of great significance in supporting Nguyen Ai Quoc to clearly determine his oriont.at.ion in leaving his homeland for search of the Vietnamese way to national salvation, th a t was, to go to the Western countries to identify the true nature of what was then called “liberty, equality, fraternity” as held by the Western bourgeoisie. Books and journals decidedly supported him in accumulating man kind's knowledge and theories of revolution-making, so as to rise from his genuine patriotism to Marxism- Lenism. Books and journals themselves became a sharp weapon for revolutionary struggles used by Nguyen Ai Quoc as a revolutionary leader, against imperialism and an important means to disseminate Marxism and Leninism into Vietnam, and to make an active preparation, ideologically and organizationally, for the coming into being of the Vietnam Communist Party.